2018
DOI: 10.1016/j.bbadis.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

GCN2 deficiency protects against high fat diet induced hepatic steatosis and insulin resistance in mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by hepatic lipid deposition and oxidative stress. It has been demonstrated that general control nonderepressible 2 (GCN2) is required to maintain hepatic fatty acid homeostasis under conditions of amino acid deprivation. However, the impact of GCN2 on the development of NAFLD has not been investigated. In this study, we used Gcn2 mice to investigate the effect of GCN2 on high fat diet (HFD)-induced hepatic steatosis. After HFD feeding for 12 weeks, Gcn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Hens FLHS commonly selected as a study model of NAFLD owning to the pathogenesis of FLHS was similar to NAFLD in humans, such as excessive triglyceride accumulation, severe hepatic steatosis, insulin resistance, oxidation stress, inflammatory reaction, and autophagy [ 16 ]. It has been demonstrated that GCN2 was a key regulator of liver fatty acid metabolism and the development of NAFLD [ 17 , 18 ]. In addition, isobutyric and isovaleric acids, generated by fermentation of BCAAs, have been confirmed that could inhibit both cAMP-mediated lipolysis and insulin-stimulated de novo lipogenesis in primary rats and human adipocytes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hens FLHS commonly selected as a study model of NAFLD owning to the pathogenesis of FLHS was similar to NAFLD in humans, such as excessive triglyceride accumulation, severe hepatic steatosis, insulin resistance, oxidation stress, inflammatory reaction, and autophagy [ 16 ]. It has been demonstrated that GCN2 was a key regulator of liver fatty acid metabolism and the development of NAFLD [ 17 , 18 ]. In addition, isobutyric and isovaleric acids, generated by fermentation of BCAAs, have been confirmed that could inhibit both cAMP-mediated lipolysis and insulin-stimulated de novo lipogenesis in primary rats and human adipocytes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…30) GCN2 gene deficiency can alleviate heart inflammation caused by a high-fat diet, thereby alleviating cardiac damage. 13) Moreover, GCN2 gene deficiency can alleviate doxorubicin-induced cardiac damage, and eIF2α gene deficiency showed similar results. 31) Therefore, inhibiting the GCN2 activity was an effective strategy for treating cardiac injury and was the mechanism underlying the relief of cardiac injury by exercise.…”
Section: Discussionmentioning
confidence: 90%
“…12) Reduced GCN2 activity may protect against heart inflammation caused by a high-fat diet and cardiac damage induced by doxorubicin through the inhibition of the eIF2α/ATF4 pathway and then inhibit the expression of inflammatory or apoptotic factors. 13) Although GCN2 is involved in inflammation and cardiac injury, its role in the exercise-preconditioning-mediated alleviation Figure 1. Experimental scheme diagram.…”
mentioning
confidence: 99%
“…Lipid accumulation and the expression of SREBP-1c were both reduced in the liver of ATF4 knockout mice [115]. Additionally, ATF4 knockout mice showed reduced lipid accumulation in the liver after HFD [116]. Exercise reduced ATF4 protein and TG content in the liver of NAFLD mice [54], indicating that exercise reduced the lipid accumulation by controlling ATF4 expression.…”
Section: Ers-related Molecular Mechanism By Whichmentioning
confidence: 96%